Low Pulvinar Intensity in Susceptibility-Weighted Imaging May Suggest Cognitive Worsening After Deep Brain Stimulation Therapy in Patients With Parkinson's Disease - Matsuura, Keita; Maeda, Masayuki; Satoh, Masayuki; Tabei, Ken-ichi; Araki, Tomohiro; Umino, Maki; Kajikawa, Hiroyuki; Nakamura, Naoko; Tomimoto, Hidekazu (Frontiers in Neurology, 2019)
Purpose: Deep brain stimulation (DBS) is an established therapy for Parkinson's disease (PD). However, deteriorating cognitive function after DBS is a considerable problem for affected patients. This study was undertaken to predict cognitive worsening based on pulvinar findings in susceptibility-weighted imaging (SWI). Methods: We examined 21 patients with PD who underwent DBS along with SWI and neuromelanin-sensitive MR imaging (NMI). We further assessed pulvinar hypointensity based on SWI findings, as well as the area of the substantia nigra (SN) pars compacta in NMI. Then we examined associations with cognitive changes, pulvinar hypointensity, and SN area. The patients’ cognitive function immediately before surgery was compared with function at one year postoperatively. Results: Pulvinar hypointensity on SWI was found in 11 of 21 patients with PD at baseline. One year postoperatively, six of the 21 patients demonstrated a Mini-Mental State Examination score that was ≥3 points lower than the baseline score. We observed pulvinar hypointensity on SWI before DBS surgery in five of these six patients (p = 0.072). During the first postoperative year, six of 21 patients reported both transient and permanent hallucinations; we observed pulvinar hypointensity in these six patients, while 10 patients without pulvinar hypointensity had no hallucinations. Conclusion: Pulvinar hypointensity on SWI in patients with PD may provide information useful for predicting cognitive deterioration after DBS treatment.